Mengkaji Al-Qur’an Sebagai Perlindungan Martabat Manusia: Studi Kasus Human Trafficking di Kamboja - Mohammad Raihan Kumala Putra (Yayasan Salam Cerdas Al-Fattah, 2025)
implications for the phenomenon of human trafficking, with a focus on cases that have befallen Indonesian citizens in Cambodia. Using the literature study method from scientific journals, books, theses, and social media content containing victim testimonies. Analysis was carried out with the stages of data reduction, data presentation, and conclusion drawing, and supported by the content analysis method of digital data. The research findings show that human trafficking is a modern form of injustice that contradicts Qur'anic values in principle, especially in verses such as Al-Isra': 70, An-Nur: 33, and Al-Baqarah: 177. Islam explicitly teaches respect for human dignity (karāmah insāniyyah), rejects slavery, and encourages liberation from all forms of exploitation. Therefore, the prevention and handling of human trafficking in an Islamic perspective must be positioned as part of the religious mandate, not just a social issue. Synergy between the state, society, and religious institutions is needed to build a system that guarantees the protection of humanity as a whole.